Aberrant expression of sonic hedgehog pathway in colon cancer and melanosis coli. Issue 8 (4th July 2013) - Wang, Zhong Chuan; Gao, Jun; Zi, Shu Ming; Yang, Ming; Du, Peng; Cui, Long
<x xml:space="preserve">Abstract</x> Objective To determine the hedgehog (Hh) signaling pathway correlated with the development of colon cancer and melanosis coli. Methods Protein and mRNA levels of Hh signaling pathway components (sonic hedgehog [Shh], protein patched homolog 1 [Ptch 1], GLI family zinc finger 1 [Gli 1] and suppressor of fused homolog [Drosophila] [Sufu]) in 127 patients with colon cancer, 36 with melanosis coli and 20 adjacent normal mucosal tissues taken from surgical specimens were evaluated using antibody staining and quantitative real‐time polymerase chain reaction. Results In adjacent normal tissue Shh and Ptch1, but not Gli1 or Sufu, were weakly expressed and mainly in the lining epithelium of the colonic mucosa. In cancerous tissues Shh and Gli1 were uniformly strong while Ptch1 was patchy and weak, and Sufu uniformly weak, which paralleled their levels of corresponding mRNA. Elevated protein levels of Shh and Ptch were significantly associated with mucinous colonic tissues. Elevated Sufu protein levels were positively correlated with the diameter and invasion of the tumor. In patients with melanosis coli, mRNA levels of Shh, Ptch1, Gli1 and Sufu were very low, which was similar to those of adjacent normal tissues; but protein levels of Shh, Ptch1 and Gli1, but not Sufu, were high, which was similar to those of cancerous tissues. Conclusions The mRNA and protein levels of Hh pathway components are aberrantly elevated in colon cancer, which may be the potential molecular classification markers. Further studies are required to determine the role of melanosis coli in the colon tumorigenesis.